Impact of a multimodal treatment of auricular keloids on the patient’s health-related quality of life: a prospective study - Helmer, Alexander; Cantillo, Marcio; Zaubitzer, Lena; Kramer, Benedikt; Rotter, Nicole; Sadick, Haneen; Häussler, Daniel (ENT, 2025)
Introduction: Auricular keloids may be associated with social stigma and impair patients’ quality of life (QoL) significantly. Little is known about the effect of different therapeutic concepts on the patient’s QoL. This study aims to investigate the QoL in patients with auricular keloids undergoing a specific multimodal therapeutic regimen. - Materials and Methods: Patients suffering from auricular keloids were treated by a multimodal treatment comprising surgical excision, intralesional triamcinolone acetonide, and subsequent application of customized magnetic pressure splints. A prospective assessment of QoL was conducted using the validated Keloid Intervention Benefit Inventory-21 questionnaire at three time points. - Results: In total, 22 auricular keloids were included in our study. All patients completed a comprehensive 1-year follow-up assessment, with an average follow-up duration of 29 months post-surgery. Quantitative analysis of QoL metrics demonstrated significant improvement of QoL at the three times of measurement (P < .0001). Significant results were also found for the subcategories general health, physical health, social interaction, and self-esteem. - Conclusion: This study underscores the necessity of assessment of QoL in keloid treatment. Our findings highlight the advantages of multimodal treatment in enhancing patients’ QoL throughout the treatment period and managing auricular keloids with low recurrence. - Trial Registration: The study was registered at the German Clinical Trials Register (Register ID: DRKS00016348, https://drks.de/search/en/trial/DRKS00016348).
Erstmals veröffentlicht: 22. April 2025
Gesehen am 12.06.2025
Nicole Rotter ist im Artikel fälschlich als Nicole Rottery geschrieben